Natal sebagai Peristiwa Historis: Menelusuri Sejarah Natal 25 Desember - William Wahyu Sembiring (DUNAMIS: Jurnal Teologi dan Pendidikan Kristiani, 2024)
Abstract. Christmas of Jesus Christ is an annual celebration whose history is often neglected. As an important part of the ecclesiastical calendar, writings about Christmas usually revolve around reinterpreting Christmas theologically. This article will review the Christmas of Jesus Christ from a historical perspective by examining ecclesiastical documents from the past as an effort to find historical evidence regarding the Christmas event of Jesus Christ on December 25. By analizing historical documents, it was showed that Christmas on December 25 was recorded in early church documents and was not merely the result of acculturation from pagan culture, thus making the church have a basis for celebrating Christmas in accordance with Divine time pattern.Abstrak. Natal Yesus Kristus adalah perayaan tahunan yang sejarahnya sering diabaikan. Sebagai bagian penting dalam kalender gerejawi, tulisan tentang Natal biasanya berkutat tentang pemaknaan ulang mengenai Natal secara teologis. Tulisan ini akan mengulas Natal Yesus Kristus dari perspektif historis dengan meneliti dokumen-dokumen gerejawi dari masa lalu sebagai usaha mencari dan menemukan bukti-bukti sejarah tentang peristiwa Natal Yesus Kristus pada tanggal 25 Desember. Dengan memperhatikan dokumen-dokumen sejarah yang tersedia, didapati hasil dari penelitian ini adalah penetapan Natal 25 Desember sudah tercatat dalam dokumen gereja mula-mula dan bukan semata-mata hasil akulturasi dari budaya pagan, sehingga membuat gereja memiliki dasar untuk merayakan Natal sesuai dengan tata pola waktu Ilahi.